The Role of Tasamuh According to Islam in maintaining National Unity and Integrity - Tolhah Toha Nawawi (Jurnal Info Sains : Informatika dan Sains, 2023)
With increasing polarization and conflict occurring at various levels of society, it is important to understand how the principles of tasamuh can be used as a basis for achieving social harmony and national unity. This research aims to explore the role of tasamuh (acceptance or tolerance) in maintaining national unity and unity in social, political and cultural contexts. This research uses a qualitative approach with descriptive methods. The results of this research confirm that the concept of tasamuh or tolerance in Islam has a fundamental role in promoting social harmony, harmony and unity in a diverse society. This study highlights the importance of respect for differences, a deep understanding of different religious beliefs and practices, and the need for open communication and constructive dialogue. The findings of this research emphasize that the application of inclusive values, respect for diversity, and a deep understanding of religious teachings and practices will form a strong basis for building a harmonious, fair and just society. In addition, research also highlights that broad knowledge and a high attitude of tolerance can contribute to encouraging broader understanding and avoiding prejudice that can trigger conflict.